2016
DOI: 10.1016/j.tmrv.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blood Donor Characteristics on Transfusion Outcomes: A Systematic Review and Meta-Analysis

Abstract: Optimal selection of blood donors is critical for ensuring the safety of blood products. The current selection process is concerned principally with the safety of the blood donor at the time of donation and of the recipient at the time of transfusion. Recent evidence suggests that the characteristics of the donor may affect short- and long-term transfusion outcomes for the transfused recipient. We conducted a systematic review with the primary objective of assessing the association between blood donor characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 61 publications
4
52
0
1
Order By: Relevance
“…3740 With regards to frequent blood donations, a recent study has demonstrated that RBCs produced by mice with mild iron deficiency have greatly decreased survival following storage and transfusion. 16 Several prospective and ongoing studies by this group and others are in progress to investigate the impact of donor characteristics (sex, donation history, iron repletion therapy) on autologous RBC recovery and survival and patient outcomes following allogeneic RBC transfusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3740 With regards to frequent blood donations, a recent study has demonstrated that RBCs produced by mice with mild iron deficiency have greatly decreased survival following storage and transfusion. 16 Several prospective and ongoing studies by this group and others are in progress to investigate the impact of donor characteristics (sex, donation history, iron repletion therapy) on autologous RBC recovery and survival and patient outcomes following allogeneic RBC transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of rigorous clinical studies that would evaluate transfusion outcomes, our current understanding of possible patient outcomes is limited to animal studies [34][35][36] or to retrospective studies that linked donor characteristics with the risk of transfusion-related mortality. [37][38][39][40] With regard to frequent blood donations, a recent study demonstrated that RBCs produced by mice with mild iron deficiency have greatly decreased survival following storage and transfusion. 16 Several prospective and ongoing studies by this group and others are in progress to investigate the impact of donor characteristics (sex, donation history, iron repletion therapy) on autologous RBC recovery and survival and patient outcomes following allogeneic RBC transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…First, a large Canadian clinical trial recently reported that age and sex of donors influenced the outcome of transfusion in recipients, more than any other factor (e.g., age of blood or pathology) (39, 40). Although there is now good evidence that there are differences between males and females in pathology and in particular in immune responses to infection or vaccines and inflammation processes, the gender issue has not been specifically addressed satisfactorily in transfusion medicine (41): this is perhaps a path for further investigation.…”
Section: Models Of Transfusion-associated Inflammation Hitmentioning
confidence: 99%
“…Thus, a similar approach in neonates and children is needed to better inform the extent and safety of, and approaches to RBC transfusion. In addition, understanding variation in donor characteristics is necessary to fully assess the effect of “vein-to-vein” variability in RBC donor characteristics on recipient outcomes [8]. Small, single center, narrowly focused studies have not, and cannot, provide sufficient data to guide neonatal RBC transfusion.…”
Section: Big Data: Need For Rbc Donor-recipient Linked Cohort Studiesmentioning
confidence: 99%